Effect of acetone vapor treatment on photoluminescence of porous nc-Si–SiOx nanostructures - Indutnyi, I.Z.; Michailovska, K.V.; Min’ko, V.I.; Shepeliavyi, P.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The effect of treatment in saturated acetone vapors on the spectral composition and intensity of photoluminescence (PL) in porous oblique deposited SiOx films is studied. As a result of this treatment followed by high-temperature annealing at the temperature 930 °C, considerable PL intensity growth and the small blueshift of PL peak position are observed in the porous, column-like structure films containing Si nanocrystals. A more intense shortwave band (peak position – 540-560 nm) appears in the PL spectrum of these structures, in addition to the longwave band (760-780 nm). Both PL bands in treated samples are characterized by monomolecular radiative recombination, which can be attributed to annihilation of excitons in silicon nanocrystals embedded into oxide matrix (longwave band) and in carbon-enriched matrix near surface of oxide nanocolumns (shortwave band). The possibility to control the PL characteristics of the porous structures in a wide spectral range by above treatment is shown.